Багатоагентні системи в Industry 4.0 - Пушко, В. В. (ХНУРЕ, 2023)
Artificial intelligence is actively used m industry. 1 tie definition of Multi Agent systems is given. The relationship between Multi-Agent systems and biological behavior in nature is described. The advantages of Multi-Agent systems are listed. The definition of Industry 4.0 is given. Industry 4.0 has evolved the concept of Cyber Physical Production Systems. The literature is analyzed and examples of the use of Multi-Agent systems and Industry 4.0 are given. Multi Agent systems are actively implemented in Industry 4.0. Their application makes it possible to develop new approaches to the solution of current problems of industry. The use of Multi-Agent systems in Industry 4.0 is a promising area for further research and will contribute to the development of the industry.